2017
DOI: 10.1093/nar/gkw1304
|View full text |Cite
|
Sign up to set email alerts
|

ADAR2 regulates RNA stability by modifying access of decay-promoting RNA-binding proteins

Abstract: Adenosine deaminases acting on RNA (ADARs) catalyze the editing of adenosine residues to inosine (A-to-I) within RNA sequences, mostly in the introns and UTRs (un-translated regions). The significance of editing within non-coding regions of RNA is poorly understood. Here, we demonstrate that association of ADAR2 with RNA stabilizes a subset of transcripts. ADAR2 interacts with and edits the 3΄UTR of nuclear-retained Cat2 transcribed nuclear RNA (Ctn RNA). In absence of ADAR2, the abundance and half-life of Ctn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
48
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 63 publications
7
48
1
Order By: Relevance
“…2A,B). Taken together, our current results and previous findings show that both ADAR1 and ADAR2 edit specific sites within Ctn RNA [40].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…2A,B). Taken together, our current results and previous findings show that both ADAR1 and ADAR2 edit specific sites within Ctn RNA [40].…”
Section: Resultssupporting
confidence: 91%
“…A,C). Recently, we have shown that ADAR2 edits several of the adenosines within the FwR and IR2 . We aimed to determine if ADAR1 too contributes to A‐to‐I editing of Ctn RNA .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent reports show that HuR can destabilize specific target transcripts in C2C12 myoblasts (61) and other cell types (62,75,76). Our data demonstrate that ARE3 and ARE4 negatively regulate Pabpn1 expression in C2C12 myotubes, and that HuR binds specifically to ARE4 in a biochemical assay.…”
Section: Discussionmentioning
confidence: 99%